Regional renal venous hypertension and left-sided varicocele - O. B. Zhukov; A. V. Verzin; P. L. Penkov (Андрология и генитальная хирургия, 2014)
One of the most frequent correctable causes of male infertility is a varicocele. The etiology and pathogenesis of varicocele to date is a matter of debate. The aim of our study was to determine the causes and incidence of regional renal hypertension in patients with leftsided varicocele. The study involved 110 patients with left-sided varicocele in age from 18 to 35 years. Algorithm for evaluation of patients with left-sided varicocele included: physical examination, ultrasound with Doppler kidney, basin area left renal vein, aorto-mesenteric portion; the scrotum with a sample Trombetta, phlebography аnd phlebotonometry basin left renal vein and the common iliac vein. Renospermatic reflux was detected in 89 (81 %), ileospermatic 12 (11 %) and mixed 9 (8 %) patients. Patients with reflux ileospermatic excluded from the study. The 96 patients with left-sided varicocele underwent venography and phlebotonometry in 37 (38.5 %) were renal venous hypertension, with 35 of them that it was due to aorto-mesenteric compression, and in 2 cases an anomaly development – annular renal vein. Our data are comparable with the results of other authors. Patients with mesenteric compressed statistically significant reduction in the diameter of renal veins in the aorto-mesenteric portion and increased blood flow in this region, and expand prestenosis left renal vein and reduce flow velocity in this region compared with the group without renal phlebohypertension. Patients with renal phlebohypertension subsequently held shunt types of operations performed in patients with normotension occlusive types of operations. An integrated assessment of patients with left-side allows to make a holistic understanding of the basic mechanisms of disease etiology and select the appropriate type of surgery.